In-hospital and web-based intervention to counteract vaccine hesitancy in very preterm infants' families: a NICU experience - Antonio Di Mauro; Federica Di Mauro; Chiara Greco; Orazio Valerio Giannico; Francesca Maria Grosso; Maria Elisabetta Baldassarre; Manuela Capozza; Federico Schettini; Pasquale Stefanizzi; Nicola Laforgia (BMC, 2021)
Abstract Background Vaccine hesitancy is a global problem, carrying significant health risks for extremely vulnerable population as that of preterm infants. Social media are emerging as significant tools for public health promotion. Our aim was to evaluate both the coverage and the timeliness of routine immunizations in a cohort of preterm infants (< 33 weeks of gestational age) at 24 months of age whose families have been subjected to in-hospital and web-based interventions to counteract vaccine hesitancy. Methods For a period of 2 years parents of preterm infants were instructed during their follow up visits by a member of the NICU team to get correct informations about vaccines from a social network page. Vaccination rates of preterm infants were assessed at 24 months of chronological age with an electronic database and compared to both general population and historical cohort. Results Coverage and timeliness of vaccinations at 24 months of age of 170 preterm infants were analyzed in December 2019. Gestational age and birth weight median (IQR) were, respectively, 31.0 (5.0) weeks and 1475.0 (843.8) g. Coverage rates were similar to those of the regional population (p > 0.05), while timeliness of administration was significantly delayed compared to the recommended schedule (p < 0.001). Age of administration was not correlated with either body weight and gestational age at birth (Spearman rank, p > 0.05). DTaP-IPV-HBV-Hib 2nd and 3rd doses, MMR and Varicella vaccines coverage data were higher compared to historical cohort (p < 0.05). Conclusion Increasing vaccine confidence through web-based interventions could have a positive impact on vaccination acceptance of parents of preterm infants, although timeliness results still delayed. There is a strong need to develop different and effective vaccination strategies to protect this very vulnerable population.